Dimensi Kuwalitas Produk dan Harga Terhadap Kepuasan Mahasiswa Terhadap Kartu Simpati - Idris, Muhammad (Jurnal Ilmu Manajemen, 2011)
Information tecnology is devloping rapidly in recent years. As a result of the rapid devlopment of information tecnology. communication tools also grown rapidly as well. One of brand communications media operators that dominate indonesia consumer market is Simpati. This study want to find out where the product quality and price influenceon consumer satisfacation. Sample of 73 respondent used student faculty of economics Universitas Muhammadiyah Palembang. The data was obtained by distributing questionnarie to the respondents directly. Analysis tools used in this study where factor analysis. Result showed that after rotation of component matric, then the component 1 contains 10 in new variable are a variablepevormance, prime card, convenience,featurs, pride the active priode information  nsp 12, toll-free and pulse the internet. While telephone and SMS pulse component are not influence in this one. While the components contain only four variable multikolinieritas test, Where the fourth variable has a high correlation. Overall, the dimensions of the product and the price has a positive impact on customer  satisfaction